STUDY OF THE INFLUENCE OF THE EXPLOITATION PERIOD ON THERMAL PHYSICAL PROPERTIES OF DIFFERENT TYPES OF THERMAL INSULATION OF WALL ENCLOSURE STRUCTURES - БАСОК, Б. І.; ПРИЙМАК, О. В.; ГОНЧАРУК, С. М.; ПАСІЧНИК, П. О. (Technologies and Engineering, 2023)
Purpose. The purpose of the study is an experimental analysis of the behavior and changes in thermophysical properties of the most widely used thermal insulation systems during their entire operational life. Method. In order to study the thermophysical properties of various options for the thermal insulation of wall-enclosing structures, measures were taken to modernize the administrative building and a complex for the study of heat losses was developed. A comparison of experimental data obtained during the operation of heat-insulating structures over a long period of operation is carried out. Results Experimental data on temperature fluctuations and the distribution of heat flow density of a thermomodernized section of a wall-enclosing structure insulated by various methods were obtained from February 16–17, 2013 and January 16–17, 2022, and a comparison of the values of the actual coefficients of thermal conductivity of various heat-insulating materials in the first approximation was carried out. Scientific novelty. The need to assess the influence of the service life on the thermal and physical properties of heat-insulating materials used in thermomodernization of buildings of various purposes is experimentally substantiated. Practical significance. An important factor that is not taken into account when designing heat-insulating shells is presented and constructed, and the way of its research is indicated.